Genes From Epithelial-Mesenchymal Transition Predict Overall Survival Effectively in Breast Cancer: A Novel Risk Model Based on Initial Step of Tumor Metastasis. - Liang, Wei; Wang, Zi-Ying; Shao, Quan-Feng; Li, Yuan-Yuan; Zhu, Bei; Qin, Xi-Hu; Chen, Wei-Xian (Breast Cancer: Basic & Clinical Research, 2026)
Background: Accumulating evidence has demonstrated that epithelial-mesenchymal transition (EMT) plays a critical role in breast cancer (BRCA) initiation, invasion, metastasis, and prognosis. Objectives: To develop and validate a comprehensive EMT-related gene signature for robust prognosis prediction in BRCA. Design: Retrospective multi-cohort study. Methods: We obtained 1223 BRCA samples from The Cancer Genome Atlas (TCGA) and 1184 EMT-related genes from the dbEMT2.0 public database. Prognostic genes were selected via univariate Cox and LASSO regression analyses to construct a risk score model, which was subsequently validated in independent internal cohort (TCGA) and external cohorts (UCSC and GEO). Finally, a nomogram integrating the risk score with clinical parameters was established. Results: A 15-gene EMT signature was identified and used to stratify patients into high- and low-risk groups. The high-risk group exhibited significantly poorer overall survival in the TCGA cohort (P <.05), a finding consistently validated across 4 independent datasets (all P <.05). The risk score served as an independent prognostic factor (hazard ratio = 2.386, P <.001). The integrative nomogram, incorporating the risk score, age, and N and M stages, demonstrated moderate accuracy for survival prediction (C-index = 0.711). Conclusions: We developed and validated a novel 15-gene EMT signature and a corresponding nomogram, which provide a potential tool for prognostic stratification in BRCA patients.